Plant-Based Alkaline Fermented Foods as Sustainable Sources of Nutrients and Health-Promoting Bioactive Compounds - Owusu-Kwarteng, James; Agyei, Dominic; Akabanda, Fortune; Atuna, Richard Atinpoore; Amagloh, Francis Kweku (Frontiers in Sustainable Food Systems, 2022)
Traditional food fermentation is a practice that precedes human history. Acidic products such as yogurts and sourdoughs or alcoholic beverages produced through lactic acid or yeast fermentations, respectively, are widely described and documented. However, a relatively less popular group of fermented products known as alkaline fermented foods are common traditional products in Africa and Asia. These products are so called ‘alkaline’ because the pH tends to increase during fermentation due to the formation of ammonia resulting from protein degradation by Bacillus species. Plant-based alkaline fermented foods (AFFs) are generally produced from legumes including soybean, non-soybean leguminous seeds and other non-legume plant raw materials. Alkaline fermented food products such as natto, douchi, kinema, doenjang, chongkukjang, thua nao, meitauza, yandou, dawadawa/iru, ugba, kawal, okpehe, otiru, oso, ogiri, bikalga, maari/tayohounta, ntoba mbodi, cabuk, and owoh are produced at small industrial scale or household levels and widely consumed in Asia and Africa where they provide essential nutrients and health-promoting bioactive compounds for the population. Alkaline food fermentation is important for sustainable food security as it contributes to traditional dietary diversity, significantly reduces antinutritional components in raw plant materials thereby improving digestibility, improves health via the production of vitamins, and may confer probiotic and postbiotic effects onto consumers. In this review, we present currently available scientific information on plant-based AFFs and their role as sustainable sources of nutrients and bioactive compounds for improved health. Finally, we provide perspectives on research needs required to harness the full potential of AFFs in contributing to nutrition and health.